Factors Impacting on Clinical Competence of Nursing Student in a Problem based Learning Curriculum during Clinical Learning - Kholofelo Matlhaba (Journal of Ners and Midwifery, 2024)
Clinical competence of Nursing student depends on the supervision received during clinical learning. Supervisors in the clinical area plays an important role for Nursing student when developing their clinical competence in a clinical learning phase. During clinical learning, the expectation is that Nursing student should be able to integrate theory and practice when working with patients. This paper aims to account for those factors that affect competence during clinical learning of Nursing student through a Problem Based Learning curriculum. Thus, the paper reflects a section from a study whose objective was to investigate and outline professional nurses’ understandings of the clinical competencies of final-year Nursing student participating in a Problem Based Learning curriculum during clinical training in the North West Province, South Africa. A qualitative, explorative, descriptive and contextual research design was employed in the main study which had a target population of professional nurses in three hospitals in which the Nursing student following a Problem-Based Learning curriculum were placed for clinical learning. The study employed purposive sampling techniques with semi-structure interviews. In this paper, two themes and six subthemes are ported as follows: 1. that there was dysfunctional collaboration between all stakeholders including facilitators and professional nurses and 2. Professional nurses had attitudes towards Problem Based Learning. Clinical placements required meticulous planning and identification of specific theoretical learning which matched the practical learning requirements pertinent to the Nursing student’ training levels. It is therefore concluded that the development of the clinical competence of Nursing student in a Problem Based Learning curriculum is dependent on stakeholder collaboration.